Performance evaluation of a valveless micropump driven by a ring-type piezoelectric actuator - Zhang, Tao (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2006)
Presented in this paper is the study of the performance evaluation of a valveless micropump driven by a ring-type piezoelectric actuator. The application of this micropump is to circulate fuel inside a miniaturized direct methanol fuel cell (DMFC) power system. A theoretical model based on the theory of plates and shells is established to estimate the deflection and the volume change of this micropump without liquid loading. Both finite-element method (FEM) and experimental method are applied to verify this model. Using this model, the optimal design parameters such as the dimensions and the mechanical properties of the micropump can be obtained. Furthermore, various system parameters that will affect the performance of the micropump system with liquid loading are identified and analyzed experimentally. It is expected that this study will provide some vital information for many micropump applications such as fuel delivery in fuel cells, ink jet printers, and biofluidics